Implementasi Media Gambar Pada Keterampilan Bercerita Mata Pelajaran Bahasa Indonesia Kelas III SD IT Nurul Ilmi Kota Padangsidimpuan - Tahjuda Jambak, Lail; Nursyaidah, Nursyaidah; Harahap, Asriana (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
Elementary school education is an effort to educate and mold the life of a nation that is pious, loves and is proud of the nation and country, is skilled, creative, has good character, and is polite and is able to solve problems in its environment. Storytelling skills are the ability to retell actions or events verbally with the aim of sharing experiences or knowledge with others. Storytelling activities shape someone to be able to convey various stories and express feelings experienced. Based on a pre-survey conducted by researchers in class III Ar raji SD IT Nurul Ilmi Padangsidimpuan. On January 14 to February 14, 2025. There are still many students who are not confident when asked to come to the front of the class and the lack of student knowledge of vocabulary.The purpose of this study is to determine. Implementation of Picture Media to Improve Storytelling Skills in Indonesian Language Lessons for Grade III Students of SD IT Nurul Ilmi, Padangsidimpuan City. This study uses qualitative descriptive with the subjects of the study being students and 1 teacher of GradeIII Ar Raji. Data were collected through observation, interviews and documentation. Data were analyzed qualitatively using reduction, data presentation and conclusion drawing methods. Based on the research results, there are 4 indicators of children’s social skills that researchers observed, namely (I) Being able to understand the contents of the story well, (II) Being confident when asked to come forward to tell a story, (III) Understanding and mastering the pronunciation of the structure and vocabulary used, (IV) Applying Prelinguistic elements such as facial expressions, certain movements and tone of voice. Of the 4 indicators, the most visible in children is the indicator of Understanding and mastering the pronunciation of the structure and vocabulary used, namely 24 students out of 30 were able to understand the vocabulary and pronounce the word structure used when telling stories in class.